Open global innovation networks as enablers of frugal innovation: propositions based on evidence from India - Rajnish Tiwari; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2012)
Recent years have seen the emergence of low-cost innovations targeted at economically weaker sections of the society, seeking to align business with social welfare. In many instances, results on the ground have been, however, rather sobering as firms have generally (probably justifiably) worried that 'good quality, low price' products may cannibalize into their regular business. At the same time those very customers that were intended to benefit from the new approach have tended to shy away fearing low quality and social stigma of using cheap products. Using multiple case studies of successful affordability-driven innovations ('frugal innovations') from India we investigate how firms can effectively reduce market and technology uncertainty of product innovations targeted at price-sensitive customers. The key criteria to success seem to lie in reducing the overall cost of ownership and enhancing customer perception of quality and image. The case studies reveal that affordability-driven innovations are especially successful when firms seek recourse to open global innovation networks (OGINs) for collaborative development in all phases of the innovation value chain.
urn:nbn:de:gbv:830-tubdok-11804
Keywords: 650; frugal innovations; bottom of the pyramid; lead markets; open innovation; global innovation; India; open global innovation networks; innovation systems